Financing agricultural development in Africa : proceedings of the sixth symposium of the association of African Central Banks - Central Bank of Nigeria (Lagos : Central Bank Nigeria, 1990)
The main objective of the symposium was to afford Governors of the Association of African Central Banks as well as representatives of invited regional and international financial institutions and experts, the opportunity to exchange experiences on the intractable problem of financing the development of agriculture and to suggest practical approaches that might be adopted by central banks and governments in Africa
Includes bibliographical references.
hza 28/01/2019
Loans
Keywords: Agricultural economics; Africa